2016
DOI: 10.1177/0142723716649273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feedback on parent–child language with infants and toddlers in Korea

Abstract: The objective of this study was to investigate changes in the natural language environments of families with typically-developing infants receiving language feedback in South Korea. Volunteer parents of 99 children aged 4–16 months were randomly divided into experimental and control groups. During 6 months’ intervention, the experimental group recorded weekly day-long automatically-analyzed LENA measures of language environment and viewed feedback, while the control group recorded only baseline, mid-period and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 41 publications
4
66
3
1
Order By: Relevance
“…While the adult word counts from these annotations are not error free (cf. Oetting et al, 2009; Canault et al, 2015; VanDam and Silbert, 2016), correlation with human transcribers seems to be high enough to make it feasible to replicate and extend Hart and Risley's results using databases that are an order of magnitude larger (see, e.g., Weisleder and Fernald, 2013; Pae et al, 2016; Suskind et al, 2016). …”
Section: Databases Of Infant-directed Speech and Infant “Speech”mentioning
confidence: 76%
“…While the adult word counts from these annotations are not error free (cf. Oetting et al, 2009; Canault et al, 2015; VanDam and Silbert, 2016), correlation with human transcribers seems to be high enough to make it feasible to replicate and extend Hart and Risley's results using databases that are an order of magnitude larger (see, e.g., Weisleder and Fernald, 2013; Pae et al, 2016; Suskind et al, 2016). …”
Section: Databases Of Infant-directed Speech and Infant “Speech”mentioning
confidence: 76%
“…Other studies have discovered a link between aspects of caregiver speech and speech processing efficiency , and with children's brain responses to speech sounds (Garcia-Sierra et al, 2011;Romeo et al, 2018). (Canault, Le Normand, Foudil, Loundon, & Thai-Van, 2015), Spanish , Mandarin (Gilkerson et al, 2015), Korean (Pae et al, 2016), and Dutch (Busch, Sangen, Vanpoucke, & Wieringen, 2017). These studies found that the LENAgenerated adult word counts were not necessarily accurate; they tended to underestimate the amount of word counts in the recordings.…”
Section: The Present Researchmentioning
confidence: 99%
“…French, Mandarin and Korean (Canault, Le Normand, Foudil, Loundon, & Thai-Van, 2015;Gilkerson et al, 2015;Pae et al, 2016;. The LENA recording system was originally designed to be used in intervention programs to promote effective interactions between parents and their children.…”
Section: Assessing Language Input At Homementioning
confidence: 99%
“…Overall it seemed that LENA AWC and CT counts could be applied to the Korean language context (Pae, Yoon, Seol, Gilkerson, Richards, Ma, & Topping, 2016).…”
Section: Korea Assessmentmentioning
confidence: 99%
“…This indicated that feedback worked better for the below average group than the above average group. Korean parents whose linguistic environment was below average adapted their communicative interaction in response to linguistic feedback (Pae, Yoon, Seol, Gilkerson, Richards, Ma, & Topping, 2016).…”
Section: Korea Interventionmentioning
confidence: 99%